NGHIÊN CỨU XÁC ĐỊNH NGUYÊN NHÂN TRƯỢT LỞ KHU VỰC CẦU MÓNG SẾN, TỈNH LÀO CAI - Duẩn, Nguyễn Bá; Hải, Đặng Thanh; Minh, Vũ Đức; Hiên, Lê Thị Thúy (Vietnam Journal of Earth Sciences, 2011)
Studying to determine causes of landslide in the area of the Mong Sen bridge, Lao Cai provinceTo contribute to preventing and mitigating landslide hazards, we used the Multi-electrode Resistivity Imaging (MRI) method to determine causes of landslide that complements useful information, integrates with geological data to set scientific basics for proposing measures of reinforcement, prevention, and mitigation of the hazard loss.In the paper, we introduce some initial results of above mentioned method achieved in the area of the Mong Sen bridge, Lao Cai province.